Characterization and stability Test of Facial Spray Preparation of Neem Leaf Extract (Azadirachta indica A. Juss) as an Anti-Acne - Rahmawati, Dewi; Mayang, Tiara Sekar; Ambari, Yani (Jurnal Biologi Tropis, 2024)
Neem leaves are one of the natural ingredients used as an acne treatment. To avoid side effects from synthetic drugs, it is necessary to develop drugs from natural ingredients such as neem leaves. The aim of this research was to develop a facial spray with neem leaf extract as an anti acne-agent. This research method uses as a posttest-only design by giving different treatments to the propylene glycol concentration (5%, 10%, and 15%) and then carrying out a stability test. The stability tests carried out are organoleptic tests, homogeneity tests, pH tests, viscosity tests, microbial contamination tests, and dry time tests as preparation evaluations. The results of the stability test showed that the preparation was stable during storage at room temperature, as well as the influence of differences in propylene glycol concentration of the viscosity and drying time of the preparation. It was concluded that neem leaf extract could be formulated as a facial spray with good dosage stability.